Oxidative stress and inflammatory response in patients with psoriasis; is there any relationship with psychiatric comorbidity and cognitive functions?. Issue 4 (2nd October 2019) - Deveci, Erdem; Kocacenk, Tuba; Şahan, Ebru; Yılmaz, Onur; Öztürk, Ahmet; Kırpınar, İsmet
ABSTRACT: Objectives: Psoriasis is a chronic, inflammatory skin disease which has been linked to psychopathology. Oxidative stress and inflammation are associated with atherogenesis and neuronal stress thus, cognitive functions might be impaired in psoriasis patients. We aimed to compare psychiatric comorbidity, neurocognitive functions, oxidative stress and inflammatory cytokine levels in psoriasis patients with healthy controls, besides to evaluate the effect of oxidative stress and inflammation on comorbidity and cognitive functions in psoriasis patients. Methods: A total of 37 patients (11 male and 26 female) aged between 18 and 65 years with at least 5 years of education who applied to the Dermatology Outpatient Clinic of the study hospital between study period; diagnosed with psoriasis by physical examination and histopathological evaluation were included in the study. The control group was formed from healthy individuals working for the hospital. Sociodemographic data form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Semantic Verbal Fluency Test (K-A-S), Öktem Verbal Memory Processes Test, Auditory Consonant Trigram Test and Wisconsin Card Sorting Test were performed to all participants. In addition, blood samples of participants were analysed to assess total oxidant stress (TOS), total antioxidant status (TAS), oxidative stress index (OSI) and proinflammatory cytokines TNF-α and IL-6 levels. Results: BDI and BAI scores, TOS, OSI, TNF-α and IL-6 levels of psoriasis patients were significantly higher than controls. Besides, the cognitive domains of learning, recall and verbal fluency in psoriasis patients were shown to be impaired. The increased levels of depression and anxiety in psoriasis did not significantly affect the serum TAS, TOS and OSI levels. Increased IL-6 and TNF-α levels were not significantly related to depression in patients with psoriasis. Conclusion: Psoriasis patients have higher risk factors than healthy controls for cognitive impairment, independent of depression, inflammation and oxidative stress levels.